Surdez e educação: pais de crianças surdas e ansiedade - Ferrini, Cyntia Maria Silva (Universidade Federal de São Carlos, 2004)
A deaf child's birth brings the family into a new reality. Such reality might unchain anxiety states or not, depending on the conception the family has on deafness and deaf people as well as on interaction quality and established communication level. Facing that problem, this study aimed at getting to know the anxiety level of parents that attend orality services searching for oral interaction with their deaf children, and the anxiety level of those that attend bilingual services looking for interaction with their deaf children through the Brazilian Language of Signs (LIBRAS), homelike signs, speaking, and writing. In addition, this study has obtained and analyzed physiologic and behavioral measures of those parents that could be related to anxiety or not. For this, subjects took part in experiment sessions, where physiologic and behavioral reactions to stimuli were recorded and IDATE (Trace-Status Anxiety Inventory) was applied. The results of this study present difference among listener groups, orality and bilinguism as to the anxiety scale, with higher anxiety level among orality parents, while bilingual parents presented a higher anxiety than listener parents; however, this difference was not verified in physiologic measures, during the stimuli presentation. However, difference in those measures during experiment was found. On the other hand, behavioral categories indicated difference among groups. Having such results in mind, it would be interesting to confirm data from the anxiety scale with other scales, for instance, through application of Marilda Lipp s Stress test, the Analogical Scale of Humor, and Hamilton s scale for Anxiety.
Keywords: Educação especial; Surdez; Pais e filhos; Crianças surdas; Ansiedade; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL